Patient-Provider Communication With Older Adults About Sleep Apnea Diagnosis and Treatment. Issue 6 (2nd November 2017) - Fung, Constance H.; Alessi, Cathy; Truong, Cindy; Josephson, Karen; Hays, Ron D.; Col, Nananda; Patterson, Emily S.; Martin, Jennifer L.
Abstract : Patient–provider communication impacts adherence to therapy. We explored older adults' communication with their providers, preferences for communication, and views on communication attributes and decision aid characteristics, by conducting four focus groups. Several participants reported they had received insufficient information about their sleep apnea diagnosis and treatment options. Most participants felt that it would be helpful to have treatment information tailored to their needs, including information on the negative impact of treatment on comfort and convenience and disclosure about common barriers to adherence. Participants provided desired characteristics for a decision aid, including their preferred delivery method, content, and format. These findings have implications for how to design useful decision aids for older adults with newly diagnosed sleep apnea.